The Cytotoxicity and Anti-Inflammatory Properties of 1’s-1’-Acetoxychavicol Acetate (Aca) on Oral Cells - Sabri, Nur Umairah Atiqah; Muhammad Zahidan, Nor Syazwani; Said, Zulfahmi; Adnan, Siti Noor Adnalizawati; Ab Malik, Normaliza (UI Scholars Hub, 2025)
Objective: Mouthwash is widely used to maintain oral health by reducing the prevalence of pathogenic microbiomes. Nonetheless, chlorhexidine, a common active ingredient, is associated with side effects including teeth staining, mucosal peeling, mouth and tongue numbness. This has prompted interest in natural alternatives. This study aimed to identify the cytotoxicity and anti-inflammatory properties of 1’S-1’-acetoxychavicol acetate (ACA) isolated from Alpinia conchigera rhizome against human primary gingival fibroblast and keratinocyte (HPGF and HPGK). Methods: Cytotoxicity of ACA (1.57 mg/mL) against HPGF and HPGK was assessed using the MTT assay. Meanwhile, the anti-inflammatory property of ACA was analyzed based on the concentration of interleukin-6 (IL-6) and lactate dehydrogenase (LDH) synthesized by HPGF and HPGK in response to injury stimulation by lipopolysaccharide (LPS). Results: Treatment with ACA was non-cytotoxic to HPGF and HPGK, with cell viability maintained above 80% after 24 hours. In addition, ACA showed anti-inflammatory activity by reducing the concentration of IL-6 and LDH produced by HPGF and HPGK in response to LPS, reflecting the ACA possibly protecting the cells from inflammation. Conclusion: ACA isolated from A. conchigera rhizome demonstrated non-cytotoxic and anti-inflammatory properties in oral epithelial cells, suggesting its potential to be incorporated in the mouthwash.